2020
DOI: 10.1108/ijwbr-07-2019-0044
|View full text |Cite
|
Sign up to set email alerts
|

Looking behind eye-catching design: an eye-tracking study on wine bottle design preference

Abstract: Purpose The purpose of this study is to find out how unconscious perception and conscious reactions differ when it comes to evaluate wine bottles in a shopping shelf. It was evaluated how attention is related to subjective evaluations of interest and value in the perception of wine bottle design choices. Design/methodology/approach The experiment combined implicit eye-tracking observations and a quantitative measurement on the assessment on wine bottle designs. In total, 37 participants rated eight different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…Thus, cognitive bias could lead to a difference between the data obtained from self-reported behaviors and the actual behaviors of consumers. The difference between unconscious and conscious perceptions is in line with the results of Merdian, Piroth, Rueger-Muck and Raab [15], where significant differences between the unconscious perceptions of wine bottles and conscious purchase decisions were found.…”
Section: Study 2: Wine Tastingsupporting
confidence: 89%
See 3 more Smart Citations
“…Thus, cognitive bias could lead to a difference between the data obtained from self-reported behaviors and the actual behaviors of consumers. The difference between unconscious and conscious perceptions is in line with the results of Merdian, Piroth, Rueger-Muck and Raab [15], where significant differences between the unconscious perceptions of wine bottles and conscious purchase decisions were found.…”
Section: Study 2: Wine Tastingsupporting
confidence: 89%
“…However, most of these studies centered on self-reported importance based on memory, which can be a poor indicator of consumers’ choices [ 41 ]. In addition, the element that consumers pay more attention to does not automatically transform into a higher perception of value and interest in wine products [ 15 ]. Thus, cognitive bias could lead to a difference between the data obtained from self-reported behaviors and the actual behaviors of consumers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eye-tracking devices and software have been used as a tool to analyze the gaze of panelists when looking at imagery or video with multiple and varied applications, such as multimedia learning [15], aviation [16], tourism [17], and sports [18], among others. For food and beverages [19,20], eye tracking has been helpful in the research of warning labels on sugar levels [21], healthy labels and food choice [22], fixations in different areas of interest (AOI) [23], packaging design and type [24,25], and more complex situations, such as the influence of soundtracks on visual attention and food choice [26]. Other studies have combined eye tracking with contact sensors, such as electrodermal activity, to assess food perception [27].…”
Section: Introductionmentioning
confidence: 99%